Evaluating the Association between Clinical Characteristics with Progression-Free Survival and 3-Year Survival in Patients with Epithelial Ovarian Cancer - Brahmana Askandar Tjokroprawiro; Sonny Fadli; Budiono Budiono (Indonesian Journal of Cancer, 2021)
Background: This study was conducted to determine the association between clinical characteristics, progression-free survival (PFS), and 3-year survival in patients with epithelial ovarian cancer who underwent surgery in 2016-2017 at RSUD Dr. Soetomo. This study was carried out with the hope of contributing to services for patients with epithelial ovarian cancer to improve outcomes at RSUD Dr. Soetomo. Methods: This retrospective analytic study used medical record data. Survival analysis was done employing Kaplan-Meier and log-rank tests, while Cox regression was utilized to analyze characteristics, recurrence, and mortality. Results: In 2016-2017, 56 patients with epithelial ovarian cancer met the inclusion criteria. Clinical characteristics of residue, stage had significant associations with PFS (P-value of 0.007 and P-value of 0.005, respectively). Residue, stage, histopathology, and the number of chemotherapy cycles had significant associations with 3-year survival (P-value of 0.001, P-value of < 0.001, P-value of < 0.001, P-value of 0.031, respectively). Recurrence and stage had a significant association with the following hazard ratios: stage I HR: 1 (CI 95%, P-value 0.145), stage II HR: 6.5 (CI 95% 0.6–74.7, P-value 0.134), stage III HR: 12.2 (CI 95% 1.4–105.4, P-value 0.061), and stage IV HR: 10.4 (CI 95% 0.8–120.8, P-value 0.061). Mortality had significant associations with stage, histopathology, and the number of chemotherapy cycles, with hazard ratios as follows: stage IV HR: 43.6 (CI 95% 4.5–417.9, P-value 0.001), seromucinous histopathology HR: 20.1 (CI 95% 0.9–408.6, P-value 0.026), chemotherapy cycles < 3 HR: 3.6 (CI 95% 1.2–11.5, P-value 0.459), and > 3 HR: 1 (CI 95%, P-value 0.028).Conclusions: Residue and stage had statistically significant associations with PFS and can be predictors for disease recurrence. Residue, stage, histopathology, number of chemotherapy cycles had significant associations with 3-year survival, but only the latter three characteristics can be predictors for mortality